Polypharmacy driven synergistic toxicities in elderly breast cancer chemotherapy drug management and adverse drug reactions: a mini review - Wang, Xiran; Yang, Jin; Zhang, Jieying; Yang, Hong (Frontiers in Pharmacology, 2025)
Breast cancer is increasingly diagnosed in older women (median age ≈63 years), and chemotherapy outcomes are clouded by a polypharmacy landscape—defined here as ≥5 concurrent medications—that magnifies toxicity beyond single-agent expectations. Prospective geriatric-oncology cohorts reveal a median of eleven concomitant drugs and clinically relevant potential drug–drug interactions (rPDDI) in up to 75% of patients; each level-1 conflict almost doubles grade 3–4 non-haematological events, while polypharmacy-frailty indices outperform chronological age for predicting unplanned hospitalisation. Age-linked gastric alkalisation, cytochrome-P450 attrition and renal decline compress pharmacokinetic space: cimetidine lifts epirubicin exposure by 39%, proton-pump inhibitors halve palbociclib troughs yet heighten neutropenia, and triazole antifungals quadruple free vincristine levels, yielding neuropathy in 87% of recipients. Beyond kinetics, overlapping end-organ liabilities—anthracycline–trastuzumab cardiotoxicity, taxane-β-blocker arrhythmia, capecitabine–warfarin haemorrhage—translate polypharmacy into a synergistic toxicity premium that erodes functional independence. Pharmacist-led reconciliation coupled with algorithmic deprescribing removes ≥1 potentially inappropriate medication in 80% of elders, while electronic rPDDI alerting and DPYD/CYP2D6 genotyping halve severe events without sacrificing efficacy. Composite scores integrating regimen complexity with genomic risk and circulating toxicity markers are emerging as real-time sentinels. By weaving mechanistic, epidemiologic and implementation evidence, this review charts how polypharmacy propels synergistic toxicities in elderly breast-cancer chemotherapy and delineates stewardship frameworks poised to reconcile oncologic potency with geriatric safety.